2019
DOI: 10.1021/acsomega.9b00960
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Technical Feasibility of Betanin and Pectin Extraction from Opuntia ficus-indica Peel via Microwave-Assisted Hydrodiffusion

Abstract: Investigating the feasibility of betanin and pectin extraction from Opuntia ficus-indica peel via microwave-assisted hydrodiffusion and gravity, this study identifies selected important economic and technical aspects associated with this innovative production route starting from prickly pear fruit discards. Which benefits would be derived from this process? Would production be limited to Opuntia -growing countries or, likewise to what happens with dried lemon peel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, currently, there is little or no available literature on the disintegrating properties of pectin. It has been reported that sourcing pectins from plants with short maturity and investigating their disintegrating and other tablet formulation properties will diversify their use in the pharmaceutical industry and attract huge revenues for pharmaceutical industries involved in this research [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, currently, there is little or no available literature on the disintegrating properties of pectin. It has been reported that sourcing pectins from plants with short maturity and investigating their disintegrating and other tablet formulation properties will diversify their use in the pharmaceutical industry and attract huge revenues for pharmaceutical industries involved in this research [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using agricultural waste, durian peel, can reduce waste disposal and burning that causes several environmental pollutants and, at the same time, improve the economic value of durian peels [2]. The world's market demand for pectin has been growing quickly (> 7 % annual growth rate) due to the expanding consumer base for low-calorie and lowfat food products [41]. Moreover, the market size of pectin is expected to expand more rapidly than gelatin and starch [42].…”
Section: Economic and Environmental Benefits Of Extracting Pectin Fro...mentioning
confidence: 99%
“…OFI peels are rich in proteins, vitamins, minerals, and carbohydrates (dietary fiber and pectin) as well as bioactive substances known for their source of beneficial properties. Numerous studies have been published that found that OFI peels have multiple physiological activities such as antioxidant, antiinflammatory, antimicrobial, and anti-acetylcholinesterase [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%